Free and Bound Phenolic Profiles of Rosa roxburghii Tratt Leaves and Their Antioxidant and Inhibitory Effects on α-Glucosidase - Yang, Yuzhe; Li, Wu; Xian, Wenyan; Huang, Wei; Yang, Ruili (Frontiers in Nutrition, 2022)
Rosa roxburghii Tratt (R. roxburghii) tea is a traditional chinese beverage. The present study aims to investigate and compare the phenolics present in free and bound forms of two cultivars of R. roxburghii leaves, and their bio-activities. The total phenolic content of free and bound fractions was 72.71 and 17.75 in Gui Nong No. 5 (GNN5) as well as 94.28 and 11.19 mg GAE/g DW in Seedless Cili (SC). 37 phenolic compounds were characterized and quantified by UPLC-Q-Exactive Orbitrap/MS with most ellagic acid, quercitrin, isoquercitrin and quininic acid in free fraction, while gallic acid, ellagic acid and hyperoside were main compounds in bound form. Free fractions with higher phenolic contents also showed more excellent performances on antioxidant activity and inhibitory potency in α-glucosidase than bound phenolics. Therefore, the results highlight that R. roxburghii leaves are a promising source enriched in phenolic constituents for functional beverage or nutritional food.